2016
DOI: 10.7567/jjap.55.05fg09
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the green band in photoluminescence spectra of heavily doped AlxGa1− xN:Si with the Al content x > 0.5

Abstract: We report time-resolved and temperature-dependent photoluminescence investigations of green photoluminescence in heavily doped Al x Ga1− x N:Si films grown by molecular beam epitaxy on sapphire substrates. The green band dominates in the photoluminescence spectra of Al x Ga1− x N:Si films with the Al content higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 33 publications
1
7
0
3
Order By: Relevance
“…Its central position also shows a minor upshift by some 50 meV over this T range, although the bandgap decreases by ≈50 meV, that is there must occur some kind of thermal excitation into close lying excited initial states of the transition. Osinnykh et al reported PL spectra even up T = 1000 K, which show a further upshift by ≈100 meV as compared to the T = RT position.…”
Section: Resultsmentioning
confidence: 95%
“…Its central position also shows a minor upshift by some 50 meV over this T range, although the bandgap decreases by ≈50 meV, that is there must occur some kind of thermal excitation into close lying excited initial states of the transition. Osinnykh et al reported PL spectra even up T = 1000 K, which show a further upshift by ≈100 meV as compared to the T = RT position.…”
Section: Resultsmentioning
confidence: 95%
“…Based on transmission measurements, the acceptor involved was assigned to carbon on nitrogen site (CN) or carbon‐related complexes. Osinnykh et al studied this PL band in AlxGa1xN and found it to shift only slightly with composition variation in the range 0.5<x<1. They also suggest (CN) or a vacancy complex as the strongest candidates for the acceptor.…”
Section: Resultsmentioning
confidence: 98%
“…Интенсивное " зеленое" излучение появлялось в слоях с содержанием алюминия x = 0.6−0.7 при кон-центрации атомов кремния порядка 5 · 10 19 см −3 . В ра-боте [2] было показано, что излучение имеет донорно-акцепторный и зона-акцепторный механизмы рекомбина-ции, где донором является кремний на месте катиона, ак-цептором предположительно является трехкратно заря-женная катионная вакансия. Концентрация атомов крем-ния может быть управляемо повышена до 10 20 см −3 [3], что влияет на величину упругих напряжений и концен-трацию дефектов кристаллической решетки.…”
Section: Introductionunclassified